Computer Networks: 22nd International Conference, CN 2015, Brunów, Poland, June 16-19, 2015. Proceedings - Gaj, Piotr (Springer, 2015)
This book constitutes the thoroughly refereed proceedings of the 22st International Conference on Computer Networks, CN 2015, held in Brunów, Poland, in June 2015. The 42 revised full papers presented were carefully reviewed and selected from 79 submissions. The papers in these proceedings cover the following topics: computer networks, distributed computer systems, communications and teleinformatics.